6. Descompuneţi în factori: a) a(x+1)+ (x + 1); d) x(x + y) + y(x+y); b) a(x-1)-b(x - 1); e) x(x-y)-y(x - y); c) x(a + b) + y(a + b); f) x²(x + 1) + x(x + 1).
Răspunsuri la întrebare
Răspuns de
0
Explicație pas cu pas:
a) a(x+1)+(x+1)= (a+1)(x+1)
d) x(x+y)+y(x+y) = (x+y) (x+y) =(x+y) ^2
b)a(x-1)-b(x-1)= (a-b) (x-1)
e)x(x-y)-y(x-y)= (x-y) (x-y) = (x-y) ^2
c) x(a+b) +y(a+b) =(x+y) (a+b)
f) x^2(x+1)+x(x+1)= (x+1)(x^2+x)=x(x+1)(x+1)=x(x+1)^2
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă